Increasing Awareness of Diabetes Mellitus in The Elderly in Lamongan Regency Through Community Service - Putri , Maurilla Shafira; Salsabila , Annisa Clara; Choirunnisa’ , Aulia; Yamani, Laura Navika; Ayuningtyas , Nurul; Qona'ah , Arina; Astutik, Erni; Qurniyawati, Eny (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – The Indonesian government had a chronic disease management program, PROLANIS, targeted for diabetes and hypertension since 2010 to prevent chronic disease patients from severe complications through monitoring and control measures. The purpose of this community service was to improve the health status of diabetic patients who participate in PROLANIS in Sukodadi and Sukolilo Villages, Lamongan Regency, through analysis of blood glucose levels. Design/methodology/approach – To overcome the problems previously mentioned, community service has been proposed. This service includes educating participants about metabolic syndrome and health checks. The main aim of this educational program is to increase public awareness about diabetes mellitus. The blood examination aims to determine the prevalence of diabetes mellitus in these villages. This educational program involves direct mentoring and outreach methods, such as the creation of booklets, educational videos, and PPTs. Findings and Discussions – In Sukodadi and Sukolilo Villages, community service was organized as a response to the high prevalence of diabetes mellitus. The program included blood tests and educational sessions for participants enrolled in the PROLANIS initiative. Analysis of the data revealed that the average blood sugar level of the participants was 143.1 mg/dl, slightly above the normal blood sugar level tolerance limit of 140 mg/dl. Nevertheless, the results indicate that the blood sugar levels of the participants can be effectively managed and kept below the diabetes tolerance threshold of <200 mg/dl. Originality/value – Our community services in Sukodadi and Sukolilo Village, Lamongan Regency, showed that most elderly women with diabetes mellitus are retired. As people age, their risk of high blood glucose levels increases. Despite the average glucose level of PROLANIS participants being higher than normal, it can still be controlled. Our findings can guide the government to organize diabetes management programs and help service providers carry out prevention measures.